(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Currently in Italy, in contrast to other EU countries, a supply chain for hunted game meat does not exist. Nevertheless there are the conditions for its development (Gaviglio et al., 2017); in fact game meat dishes’ has always been part of Alpine area’s culinary tradition and furthermore, management measures aimed at reducing the overpopulation of large wild ungulates leaded to an increase in the availability of their meat. In this context, the present research aims at analyze the dynamics of the value in the local non-existent supply chain of the large wild game meat by the application on the case study of the Valle Ossola (Piedmont, Italy). Due to its representativeness among Italian wild ungulates, the research focus on red deer meat. The data has been collected in 2016 through in-depth interviews and focus groups with the stakeholders involved in the supply chain: hunters, transformers and restaurateurs. Results show that for the hunter the red deer reach a hypothetical price of 6,00 €/kg. From a meat processing targeted at the maximum enhancement of the carcass, without any waste, the transformers can reach a hypothetical price of 9,80 €/kg. Whereas for the restaurateur, the red deer meat can reach a final price range between 22,88 and 51,47 €/kg (hypothesizing maximum sales of high value-added course). Through the maximization of the meat’s quality, hunter and transformers profits can increase significantly, with a redistribution of the added value throughout the supply chain. A limitation of this study is that the calculated values does not take into consideration the stakeholders’ production costs (that increasing along the supply chain). Considering our findings, the development of sustainable supply chain of the local game meat could be economically interesting. Thus, wild ungulates could represent an economic resource for the population rather than an environmental and social cost for the mountain areas.